REAKSI PASAR MODAL INDONESIA TERHADAP PENGUMUMAN PEMINDAHAN IBUKOTA (Studi Empiris pada Perusahaan Property & Real Estate yang Listing di BEI) - Rizal Aji Pamungkas; Maslichah Maslichah; Junaidi Junaidi (e_Jurnal Ilmiah Riset Akuntansi, 2020)
ABSTRACTThe purpose of this research is to analyze the amount of Indonesian Capital Market reaction toward The Announcement of Transfer of Capital City event at the date of 26 August 2019 using Abnormal Return (AR) and Trading Volume Activity (TVA) as variable. The research population is company in the Property & Real Estate sector that listed in the Indonesian Stock Exchange. The sample were taken using purposive sampling method. The hypothesis was analyzed using Wilcoxon Signed-Rank Test. The results of this research showing that there is no significance differences in the average Abnormal Return and average Trading Volume Activity before and after The Announcement of Transfer of Capital City event. Which means that this event is didn’t have any information so the market not reacted. Keywords: Event study, Transfer of capital city, Abnormal return, Trading volume activity.